The Innovation and Leapfrog Development of Accounting Culture Confidence - Sun, Haijun (Journal of Theory and Practice of Management Science, 2023)
The era of Internet + has arrived, and it is revolutionizing people's thinking, production and life style. How does accounting culture overtake at the major historical turning point? How to keep pace with The Times and play their own value in realizing the great rejuvenation of the Chinese nation? How to establish a leading position in the world accounting culture? This is an important problem that every accountant must think deeply and solve urgently.